THE RENT COST STRUCTURE ANALYSIS OF ASSET OWNED BY SEMARANG REGIONAL - Hardiwinoto -; Akhmad Fathurohman; Ery Wibowo (Universitas Muhammadiyah Semarang, 2017)
The objective of this study is to analyze rent cost structure of asset belongs to the Semarang regional government that can be leased to private parties or third parties. Based on the rental value formulation, it can stimulate investment in Semarang. The method of analysis uses three steps. They are, firstly, to identify the assets of both types and volumes, secondly, to review of regulations and legislation applicable, and the last, to compare with that has been done in other areas. In addition, focus group discussion simulation was used for formulating the cost structure. The result of the research is a formula to determine the rental value of assetsowned by Semarang Regional Government that can be leased to private parties or third parties. Keywords: cost structure, assets, investment, PAD